PENINGKATKAN HASIL BELAJAR IPS MELALUI PENERAPAN MODEL DISCOVERY LEARNING KAJIAN DOKUMEN HISTORIS PERISTIWA-PERISTIWA MENJELANG PROKLAMASI KEMERDEKAAN INDONESIA PADA SISWA KELAS VIII.1 SMPN 3 KOTO BARU - Gusvita, Eni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
This study aims to improve the learning outcomes of social studies through the application of Discovery Learning Historical Document Review of Events Towards the Proclamation of Indonesian Independence in VIII.1 students of SMPN 3 Koto Baru. Classroom action research was carried out for two cycles, with each meeting held twice. Each meeting is carried out with the Discovery Learning Application. As a data collection tool is the result of formative tests given at the end of cycle I and end of cycle II. The results obtained from the study of social studies at the initial observation only 50% of students who reach KKM, in cycle 1 increased by 69% and increased again by 87% in cycle 2. Social studies learning outcomes have improved from the first cycle to the second cycle, this shows that the Discovery Learning model of the Historical Document Review of the Events Towards the Proclamation of Indonesian Independence can be used as an alternative learning to improve student learning outcomes.